Heterogeneous austenite grain growth in martensitic 9cr steel: coupled influence of initial metallurgical state and heating rate. (October 2013) - Zavaleta Gutiérrez, N.; Luppo, M. I.; Danon, C. A.; Toda-Caraballo, I.; Capdevila, C.; García de Andrés, C.
Abstract : The coupled influence of the initial metallurgical state and the heating rate to austenite on the occurrence of heterogeneous grain growth during austenitisation of an ASTM A213–T91 steel has been studied. To that aim, two-step thermal cycles were designed. In the first step, different starting metallurgical conditions were obtained by treating the as received material at 780°C for increasing times up to 6 h. In the second step, in situ austenitisation was performed by heating to austenite at rates of 1, 30 and 50°C s −1 and then holding at 1050°C for 30'. Two types of austenite grain structures were obtained after austenitisation, namely, homogeneous and heterogeneous. The homogeneous structure was characterised by a smooth size distribution of approximately equiaxed, normally grown grains. The heterogeneous structure, instead, exhibited the exaggerated growth of a few austenite grains embedded in a small to medium sized matrix. For the 1°C s −1 heating rate and all of the initial metallurgical states, only homogeneous grain growth was observed, whereas for the 50°C s −1 heating rate only heterogeneous grain growth was observed regardless the starting metallurgical condition. Instead, the occurrence of homogeneous or heterogeneous grain growth after heating at 30°C s −1 was observed to be a function of the time of previous tempering. Some explanations of the phenomenon are advanced taking into account the precipitation state of second phases.